2012
DOI: 10.1016/j.jenvman.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of landfill leachate by using lateritic soil as a natural coagulant

Abstract: In the last several years, the interest on domestic wastewater treatment has increased due to the rise of water consumption resulted from the world population growth. The excessive use of inorganic coagulants, such as aluminum sulphate, in domestic wastewater treatment processes contributes to generate high negative environmental impacts and risks to living organisms. Besides its low biodegradability, as aluminum sulphate increases metal content in discharged effluents rises, generating toxic sludge. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Single use of PAC showed that turbidity, 99.18 %; color, 97.26 % and TSS, 99.22 % were achieved; whereas alum showed inferior removal (turbidity, 94.82 %; color, 92.23 % and TSS, 95.92 %) (Ghafari et al 2010). Liu et al (2012) Syafalni et al (2012) compared lateritic soil coagulant with alum in jar test experiment. The optimum condition was achieved at pH 2 and lateritic soil coagulant dose of 14 g/L resulting 65.7 % COD, 81.8 % color and 41.2 % NH 3 -N removal.…”
Section: Coagulation Flocculationmentioning
confidence: 98%
“…Single use of PAC showed that turbidity, 99.18 %; color, 97.26 % and TSS, 99.22 % were achieved; whereas alum showed inferior removal (turbidity, 94.82 %; color, 92.23 % and TSS, 95.92 %) (Ghafari et al 2010). Liu et al (2012) Syafalni et al (2012) compared lateritic soil coagulant with alum in jar test experiment. The optimum condition was achieved at pH 2 and lateritic soil coagulant dose of 14 g/L resulting 65.7 % COD, 81.8 % color and 41.2 % NH 3 -N removal.…”
Section: Coagulation Flocculationmentioning
confidence: 98%
“…1 (a), at PAC concentration of 108.8 ppm, the boron removal efficiency was above 55%. High coagulant doses content helps in destabilization of the colloidal particles in solution (Syafalni et al, 2012). Fig.…”
Section: Resultsmentioning
confidence: 98%
“…As stated by Shaylinda et al [2], a composite coagulant is made by combining two types of coagulants as one reagent by premixing the coagulants through certain working conditions. The substitution of chemical coagulants with natural materials can be applied to reduce the adverse effects, simplify the dosing process, and tackle other drawbacks [2,4]. The operation using a composite coagulant is more convenient as it shortens the treatment process and practical from a nancial perspective.…”
Section: Development Of Composite Coagulantmentioning
confidence: 99%